Development of controllers for wind power plants - Kalpani Jayamalee Thantirige (2013)
Increasing CO2 emissions have become a global concern nowadays and demand for electrical energy also has increased significantly. Therefore, renewable energy sources have prominent place in the energy market. During past few decades, wind power cause clean revolution in the energy sector and become one of the most resourceful sustainable technology around the world. Large scaled wind farms have been installed in both onshore and offshore. The variable speed wind turbines are predominantly deployed in WECSs which are driven by Doubly Fed Induction Generator. Actually, conventional power converters are also required to enhance further with suitable control schemes because of the rapid growth of the wind turbines power rating.